Lipid Nanoparticles Carrying Essential Oils for Multiple Applications as Antimicrobials - Elenice Francisco da Silva; Fernanda Aparecida Longato dos Santos; Henrique Machado Pires; Luciana Machado Bastos; Lígia Nunes de Morais Ribeiro (Pharmaceutics)
Lipid nanoparticles (LNPs) are versatile delivery systems with high interest because they allow the release of hydrophobic and hydrophilic molecules, such as essential oils (EOs) and plant extracts. This review covers published works between 2019 and 2024 that have reported the use of essential EO-based LNPs with antimicrobial properties and applications in human and animal health, as well as biopesticides. In the human healthcare field, reports have addressed the effect of encapsulating EOs in lipid nanosystems with antiviral, antibacterial, antiprotozoal and antifungal activities. In animal care, this still needs to be more deeply explored while looking for more sustainable alternatives against different types of parasites that affect animal health. Overall, the antibacterial activities of LNPs carrying EOs are described as alternatives to the use of synthetic antibiotics. In the field of agriculture, studies showed that these approaches in the control of phytopathogens and other pests that affect food production. There is a growing demand for innovative and more sustainable technologies. However, there are still some challenges to be overcome in order to allow these innovations to reach the market.